2009
DOI: 10.4049/jimmunol.0901786
|View full text |Cite
|
Sign up to set email alerts
|

Selective Down-Regulation of Neutrophil Mac-1 in Endotoxemic Hepatic Microcirculation via IL-10

Abstract: Hepatic neutrophil adhesion during endotoxemia is an integrin-independent, CD44-dependent process. Because integrins function in other endotoxemic vasculatures, we used spinning disk confocal intravital microscopy to assess whether LPS down-modulated integrin functions in sinusoids. First, we applied fMLP onto the liver surface, and compared it with systemic LPS administration. Local fMLP caused neutrophil adhesion, crawling, and emigration for at least 2 h. Surprisingly, the number of adherent and crawling ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(82 citation statements)
references
References 49 publications
8
73
0
1
Order By: Relevance
“…4), it is possible that IL-10 supplementation increases the colonization of the liver by the 32777⌬yopM mutant by reducing bactericidal activity in PMNs. The exposure of PMNs to IL-10 has been shown to reduce phagocytic activity and the expression of cytokines (3), and high levels of intrahepatic IL-10 cause the downregulation of Mac-1 on PMNs (30). Thus, IL-10 supplementation may decrease PMN function and maintenance at this site, thereby creating a permissive site for the replication of the 32777⌬yopM mutant in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…4), it is possible that IL-10 supplementation increases the colonization of the liver by the 32777⌬yopM mutant by reducing bactericidal activity in PMNs. The exposure of PMNs to IL-10 has been shown to reduce phagocytic activity and the expression of cytokines (3), and high levels of intrahepatic IL-10 cause the downregulation of Mac-1 on PMNs (30). Thus, IL-10 supplementation may decrease PMN function and maintenance at this site, thereby creating a permissive site for the replication of the 32777⌬yopM mutant in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to correlate the effects of aPC on the LPS response of DCs with alterations in the chemokine/cytokine milieu in the plasma compartment and whole spleen lysates or via direct detection of intracellular IL-12 as a key modulator of DC function were not informative. Recent reports on the antiinflammatory effects of IL-10 in liver injury (47,48) and in the suppression of graft-versus-host disease by CD8 + DCs suggest that the statistically significant augmentation of IL-10 levels may be biologically relevant and possibly result from the interaction of EPCR + DCs with T cells (49). How aPC treatment affects the above candidate mechanisms and how they might contribute to mitigating the lethal effects of LPS challenge remains to be clarified.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it had previously been demonstrated that neutrophils could utilize b 2 integrins to mediate all steps in the recruitment cascade (tethering, rolling, and adhesion) in the splanchnic circulation when shear rate was reduced by 50% (similar to the shear encountered in the slow-flowing sinusoids) (Gaboury and Kubes 1994). Nevertheless, numerous studies have observed that neutrophil recruitment to the septic/ endotoxemic liver is unaffected by blockade or genetic deficiency of b 2 integrins or their endothelial ligand intercellular adhesion molecule 1 (ICAM-1) (Jaeschke et al 1996;McDonald et al 2008;Menezes et al 2009;Wong et al 1997). Finally, while a 4 integrin/vascular CAM 1 (VCAM-1) interactions are not generally thought to support neutrophil recruitment to inflamed tissues, neutrophils from patients with severe sepsis have up-regulated expression of a 4 integrin and can adhere to VCAM-1 in vitro (Ibbotson et al 2001).…”
Section: Microvasculaturementioning
confidence: 99%